Pejibaye palm (Bactris gasipaes) propagative structures and seedlings morphological study - Filho, Carlos F. Damião [UNESP]; Môro, Fabíola V. [UNESP]; Môro, José R. [UNESP]; Taveira, Leontino R. [UNESP] (My University, 1999)
Palm of Arecoideae subfamily, the pejibaye palm occurs mostly at Tropical America areas, and has achieved outstanding economic importance for heart-of-palm production with traditional farming. This work aimed to describe and record propagation structures and seedlings, throughout the different stages of their germination process, since this species is mainly propagated by seeds. The seeds were set for germination on trays with cotton and sterilized water. Representative samples were taken out from each of the different germination stages. They were photographed and drafted using a clear chamber. The propagation structures and seeds external surface were outlined and photographed. The seeds were longitudinally cut for observation and documentation of the inner morphology. The first germinative event was the growth of an undifferentiated, approximately globular cells mass, which emerged from the micropilar depression. Then, the cells mass acquired a cylinder aspect, with the early shoot and root differentiation taking place. Later, there was evidence of primary root and aerial portion. This shoot was coated by a closed and chlorophylled sheath. A lateral root outgrown at the primary root's base and an adventitious root became visible at the embryonic axis. Three other sheaths evolved at the shoot, unrolling one at a time, allowing, finally, the emergence of the primary leaf which is bifid and has parallel veins, typical of its family. Internally, an haustorial structure was developed and seemed to be related with the digestion of the endosperm, occupying, gradually, all the seed's internal space.
Keywords: Arecaceae; Germination; Plantlets